Longitudinal difference in total electron content over the East Asian region: Feature and explanation. (October 2016) - Yu, Shimei; Xiao, Zuo; Zhao, Biqiang; Zhang, Donghe; Hao, Yongqiang
Abstract: The mechanism of the longitudinal difference of ionospheric electron density is in general attributed to the thermospheric wind effect modulated by the local geomagnetic declination. Although this mechanism is tested in many case studies, there are other possible factors such as solar activity and so on which still need further investigations. In this paper, TEC data from two Chinese GPS stations located at almost same geographic latitudes but with a wide longitude span ( 38°) are used to study the morphological features of longitudinal differences under various geophysical conditions. A parameter R ew is defined as a normalized measure of the TEC difference between the two stations. All the observed temporal variations of R ew are analyzed statistically, with the results showing that negative east-west differences (Western TEC>Eastern TEC) in the noontime are pronounced during Day of Year (DoY) 90–270, while nighttime positive differences (Western TEC<Eastern TEC) are around DoY 60–90, and 270–300. All above observed features are examined by the dynamic effect of thermospheric wind using the HWM07 model. The results show that although the zonal wind does play an important role on average, it is not sufficient to explain all the observed features, the longitude dependence of the meridian wind must be considered. Finally, we observed a new feature characterized by the summer nighttime positive value in R ew which could be related to a Midlatitude Summer Night Anomaly (MSNA) phenomenon. So, it is also concluded that besides the thermospheric wind effect, other mechanisms such as the longitudinal dependence of the plasmaspheric downward flux should also be taken into consideration in explaining the longitudinal differences in the ionosphere. Highlights: TEC longitudinal effect is studied at two Chinese stations with a wide longitude span ( 38°). Nighttime equinoctial unusual increase of the E-W difference index is observed. The zonal and meridian wind, geomagnetic field and plasmaspheric downward flux all play roles in longitudinal effects of TEC.